2014
DOI: 10.1155/2014/253731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Final Impression Techniques for Management of Resorbed Mandibular Ridge: A Case Report

Abstract: The history of complete denture impression procedures has been influenced largely by the development of impression materials from which new techniques and ideas arose. The purpose of this study was to compare the retention of complete dentures made by using different impression techniques like conventional, admixed, all green, and functional techniques. The results showed that there was significant difference in retention between the six techniques where functional technique showed the highest mean value of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…18 Several studies have indicated that prosthodontic management of anthropic mandibular ridges can be very challenging. 59,60 The present case report successfully combines the advantage of CAD/CAM technology and traditional clinical recording methods for the construction of complete dentures in atrophic alveolar ridges. The presented workflow is completely functional because the clinician does not need to have either an intraoral or laboratory scanner to offer CAD/CAM dentures to patients.…”
Section: Discussionmentioning
confidence: 97%
“…18 Several studies have indicated that prosthodontic management of anthropic mandibular ridges can be very challenging. 59,60 The present case report successfully combines the advantage of CAD/CAM technology and traditional clinical recording methods for the construction of complete dentures in atrophic alveolar ridges. The presented workflow is completely functional because the clinician does not need to have either an intraoral or laboratory scanner to offer CAD/CAM dentures to patients.…”
Section: Discussionmentioning
confidence: 97%
“…4,22,23 Estas diferenças estarão certamente relacionadas com a escolha do material de impressão, do espaçamento utilizado, do biótipo dos tecidos moles de suporte e das preferências profissionais. [24][25][26] As moldeiras individuais para a realização de impressões definitivas, podem ser realizadas em diversos materiais. Neste estudo, verificou -se que o material mais utilizado para a sua confeção foi o Triad ® Dentsply, uma resina acrílica fotopolimerizável.…”
Section: Discussionunclassified
“…The advantage of this technique is that extension and pressure is obtained according to the patient's functional. 8,10 In this paper, the management of flat ridge and flabby ridge in one ridge would be discussed. The problem that arises in this case is that for obtaining a retentive denture base and optimal extension of the denture base for flat ridge, we would need a closed mouth impression technique, but this technique is contraindicated for flabby ridge because it will depress the flabby tissue.…”
Section: Introductionmentioning
confidence: 99%